SUBSTANTIATION OF THE PARAMETERS OF THE GRADER OF THE COMBINED UNIT FOR TILLING THE SOIL IN THE ROW-SPACING PLANTS IN GARDENING - Xudoyberdiev, T.S.; Baltabaev - c.t.s, B.R.; Abdumannopov, A.M. (International Journal of Psychosocial Rehabilitation, 2020)
WE know that, one of the factors of effective utilization of main field in row interspaces of gardening is qualitative softened soil grader in time. Therefore it is important to choose the right parameters of the given grader so that to level the land in high quality. The article is written on the basis of research results. Here we have given bending corner of the gathered soil clot before the grader as β and the curving corner from vertical plainness as γ and we have based its increase. The contradiction of the grader increases with the rise of its height. That is why the curviness of the grader and the outer curviness of soil clot play a great role. As the curviness of the grader rises, the contradiction decreases. The decrease of the contradiction of γ between 30° and 40° is due to the increase of soil clot from the grader. We have identified the reason of the increase of contradiction when B corner is equal to β=20°. Here, the contradiction increases as more soil is absorbed than when the corner B is equal to β=30° so that to make a soil clot.